Pattern of Childhood Poisoning and Intoxication in AL Salam Hospital Sadah -Yemen - AL Bahlooly, Mohammed A. H.; AL-Kubati, Abdulkhaliq S.; AL-Selwi, Abdulhkem A.; Al-Bahlooli, Saeed H. (Thamar University Journal of Natural & Applied Sciences, 2023)
Background and objectives: The poisoning among children is a pediatric emergency and a worldwide problem that vary in different part of the world. The study aims to investigate the clinical profile and outcome of childhood poisoning and intoxication in Yemen.Patients and methods: All patients admitted to pediatrics wards in A-Salam Hospital -Sadah governorate for ingestion of poisons over period from January 2010 to December 2011 were included in this retrospective descriptive study. The targeted group was age between 6 months and 14 years of age. The data was collected from medical records retrospectively and was analyzed with SPSS 12.0 software.The results: Total number of cases was 660 patients. They were 368 (55.8%) females and 292 (44.2%) males with female to male ratio of 1.26:1 with age ranging from 6 months to 14 years. Of these, 476 patients (72.1%) were